ADDRESSING CULTURAL DIFFERENCES IN THE TRANSLATION PROCESS - Bokieva Muharramoy Ne'matjon kizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Translation is not merely a linguistic task but a complex process that involves navigating cultural nuances to ensure meaning is accurately conveyed across languages. This thesis explores the role of cultural differences in the translation process, highlighting challenges, strategies, and their implications for effective communication. By analyzing theoretical frameworks and practical examples, the study identifies methods to address cultural barriers, including adaptation, localization, and cultural sensitivity training. The findings emphasize the importance of cultural competence in producing translations that are both accurate and culturally relevant.